2022
DOI: 10.1039/d2ra05201f
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable synthesis of biomass-derived carbon quantum dots and their catalytic application for the assessment of α,β-unsaturated compounds

Abstract: Boosting the catalytic activity of carbon quantum dots for the assessment of α,β-unsaturated compounds by microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Carbon materials at the nanoscale have unlocked new frontiers in catalysis by the development of state-of-the-art unique catalytic materials. Carbon quantum dots (CQDs) are zero-dimensional carbon-based nanomaterials and have attracted considerable interest due to their exceptional biocompatibility, low toxicity, resistance to photobleaching, tunable luminescence properties and high-temperature stability. As a result, they show growing applications in sensing, bioimaging, drug delivery, and medical diagnosis, LED production, energy conversion and storage, and so on. Recently, CQDs are recognized as a facial, effective sustainable catalyst in synthetic organic chemistry because of their assessable surface functional groups. , Owing to their distinct applications numerous methodologies have been developed for their synthesis such as arc discharge, laser ablation, electrochemical oxidation, acidic oxidation, thermal combustion, hydrothermal oxidation, microwave pyrolysis of different chemical-based carbon sources .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials at the nanoscale have unlocked new frontiers in catalysis by the development of state-of-the-art unique catalytic materials. Carbon quantum dots (CQDs) are zero-dimensional carbon-based nanomaterials and have attracted considerable interest due to their exceptional biocompatibility, low toxicity, resistance to photobleaching, tunable luminescence properties and high-temperature stability. As a result, they show growing applications in sensing, bioimaging, drug delivery, and medical diagnosis, LED production, energy conversion and storage, and so on. Recently, CQDs are recognized as a facial, effective sustainable catalyst in synthetic organic chemistry because of their assessable surface functional groups. , Owing to their distinct applications numerous methodologies have been developed for their synthesis such as arc discharge, laser ablation, electrochemical oxidation, acidic oxidation, thermal combustion, hydrothermal oxidation, microwave pyrolysis of different chemical-based carbon sources .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sun et al confirmed that polyaniline exhibits superior catalytic performance compared to conventional metal-based catalysts and commonly used N-doped carbocatalysts in the degradation of methyl orange (MO). 13 Similarly, Ait El Fakir et al demonstrated that hematite sand coated with nitrogenrich polymers (polypyrrol and polyaniline) could effectively activate PS for the degradation of organic pollutants. 17 Despite the extensive research on catalysts, there has been relatively limited exploration of sulfur-rich carbocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Carbocatalysts have gained a great deal of attention due to their biocompatibility, high catalytic activity, and eco-friendliness. 13 Additionally, they have been confirmed to effectively activate oxidants (peroxymonosulfate and persulfate (PS)) without causing secondary pollution. 14 Annamalai et al reported that carbocatalysts, particularly those doped with heteroatoms such as nitrogen, phosphorus, and sulfur, have shown remarkable catalytic activity in activation.…”
Section: Introductionmentioning
confidence: 99%
“…170 Currently, a large number of researchers have now started to use biomass materials widely available in nature. They have successfully prepared biomass-based CQDs using materials such as sh scales, 19 peanuts, 20 holy basil, 21 sweet potato peels, 22 tea leaves, 23 mangoes, 24 caffeine, 25 lignin, 26 starch 27 and soybeans 28 as the initial carbon source. The use of biomassbased preparation of CQDs can not only reduce the cost of raw materials in the preparation process and realize the multiple recycling of waste resources, but also the CQDs prepared in this way usually have very excellent biocompatibility and good uorescence emission properties, and can directly select green and pure natural precursors from the source, which greatly improves the feasibility of green environmental protection.…”
Section: Introductionmentioning
confidence: 99%